Estudo da eletro-oxidação de álcoois em catalisadores do tipo PtSnNiTi para aplicação em células a combustível - Caliman, Cristiano Carrareto (2013)
Electrocatalysts of type C/PtSnNiTi were prepared by thermal decomposition of polymeric precursors. The physico-chemical and electrochemical characterization of the electrocatalysts was performed by different techniques: X-ray diffraction, transmission electron microscopy, cyclic voltammetry and chronoamperometry. The X-ray diffraction results showed that the electrocatalysts comprise mainly Pt metal with face-centered cubic crystal structure and particle sizes ranging from 1.8 to 8.3 nm. In transmission electron microscopy analysis the average particle sizes observed were between 4 and 6 nm. The electrocatalysts were evaluated in the absence and presence of ethanol and glycerol in sulfuric acid medium. All showed activity towards alcohols oxidation. Furthermore, the Pt50Sn20Ni25Ti5 electrocatalyst showed the best results of cyclic voltammetry and chronoamperometry in presence of glycerol and ethanol respectively. The greater potency density obtained in cell tests was 20 mW/cm2 for the composition Pt50Sn20Ni25Ti5. Cyclic voltammetry data obtained in this study indicate that the addition of Ni and Ti in PtSn electrocatalysts increases its electrocatalytic activity toward alcohols oxidation